The Characteristics of Stunting Toddlers in Kairane Village Kupang Regency - Maria Goreti Pantaleon (Poltekkes Kemenkes Kupang, 2022)
Stunting is nutritional status based on the index of body length for age (PB/U) or height for age (TB/U) which is the equivalent of the terms stunted (short) and severely stunted (very short). A child who is stunted often looks like a child of normal height for his age. Stunting begins before birth due to poor maternal nutrition during pregnancy, bad eating habit, deficiency in food quality, and the intensity of frequent disease (Supariasa, 2011). Based on the Nutrition Status Observing (PSG) data, the prevalence of stunted toddlers in Indonesia has increased in 2016 from 27.5% to 29.6% in 2017 while in 2018 the percentage of 37.2% the toddlers in Indonesia had inappropriate height regarding to their age (short), currently approximately 8 million Indonesian children are experiencing suboptimal growth (Ministry of Health 2018). The objective of this study was to recognize the description of stunting toddlers in Kairane village, Kupang Regency. The samples in this study were 23 stunting toddlers in Kairane village. This research was conducted in Kairane village in May to July 2021. The results showed that most of the fathers of stunting toddlers worked as farmers (82.7%), and the mothers of toddlers were did not work or housewives (95.7%). The average numbers of family members of stunting toddlers are 5 people, and regarded to breastfeeding history, most stunting toddlers do not receive exclusive breastfeeding (69.6%).